The impact of an experimentally induced increase in arterial blood pressure on left ventricular twist mechanics - Balmain, B.; Stewart, G.; Yamada, A.; Chan, J.; Haseler, Luke; Sabapathy, S. (Wiley-Blackwell, 2016)
© 2015 The Authors. Experimental Physiology © 2015 The Physiological Society New Findings: What is the central question of this study? Increases in blood pressure elicited by isometric hand-grip exercise (IHG) have been shown to impair ventricular twist mechanics. However, the utility of the IHG model is confounded by a concurrent increase in heart rate, which independently influences ventricular mechanics. What is the main finding and its importance? We show that a period of post-IHG circulatory occlusion isolates the effect of an arterial blood pressure increase from heart rate and magnifies the impairment of left ventricular twist when compared with IHG alone. A protocol using IHG followed by brief circulatory occlusion may serve as a useful tool in examining and understanding the relationships between afterload and cardiac function in various disease states. The effects of isometric hand-grip exercise (IHG) coupled with a period of postexercise circulatory occlusion (OCC; known to sustain exercise-induced increases in blood pressure while facilitating a decrease in heart rate) on left ventricular (LV) twist mechanics was examined. Two-dimensional speckle-tracking echocardiography was used to assess LV apical and basal rotation and LV twist in 19 healthy participants (23 ± 2 years old) at rest, during 3 min of IHG (performed at 40% maximal voluntary contraction) and 3 min of OCC immediately following IHG. The IHG elicited significant (P  <  0.001) increases in mean arterial pressure (rest, 91 ± 1 mmHg; IHG, 122 ± 2 mmHg) and heart rate (rest, 65 ± 2 beats min -1 ; IHG, 91 ± 4 beats min -1 ). Mean arterial pressure remained elevated during OCC (116 ± 2 mmHg; P  <  0.001 versus rest), whereas heart rate returned to resting levels (68 ± 3 beats min -1 ; P = 0.159 versus rest). Apical rotation decreased significantly (P  <  0.01) by 10 ± 5% during IHG and 21 ± 4% during OCC, whereas basal rotation remained unchanged from rest. Left ventricular twist decreased from rest to IHG (12 ± 5%; P = 0.015) and OCC (21 ± 4%; P = 0.001), whereas a decrease in LV untwist rate was observed only during OCC. An increase in blood pressure generated by IHG, and maintained by a period of OCC, impairs aspects of LV twist mechanics. Postexercise circulatory occlusion isolated the effect of the arterial blood pressure rise (from heart rate), magnifying the impairment of LV twist mechanics when compared with IHG, whilst also negatively impacting LV relaxation. We propose that a protocol using isometric exercise followed by circulatory occlusion provides a method for studying the effects of blood pressure changes on LV twist mechanics.